Expression Profiling Analysis of the SWEET Gene Family in In Vitro Pitaya Under Low-Temperature Stress and Study of Its Cold Resistance Mechanism - Youjie Liu; Hanyao Zhang; Ke Zhao; Xiuqing Wei; Liang Li; Yajun Tang; Yueming Xiong; Jiahui Xu (Plants, 2024)
Pitaya (Hylocereus undatus) fruit is an attractive, nutrient-rich tropical fruit with commercial value. However, low-temperature stress severely affects the yield and quality of pitaya. The relevant mechanisms involved in the response of pitaya to low-temperature stress remain unclear. To study whether the SWEET gene family mediates the response of H. undatus to low-temperature stress and the related mechanisms, we performed genome-wide identification of the SWEET gene family in pitaya, and we used ‘Baiyulong’ tissue-cultured plantlets as material in the present study. We identified 28 members of the SWEET gene family from the H. undatus genome and divided these family members into four groups. Members of this gene family presented some differences in the sequences of introns and exons, but the gene structure, especially the motifs, presented relatively conserved characteristics. The promoter regions of most HuSWEETs have multiple stress- or hormone-related cis-elements. Three duplicated gene pairs were identified, including one tandem duplication gene and two fragment duplication gene pairs. The results revealed that the SWEET genes may regulate the transport and distribution of soluble sugars in plants; indirectly regulate the enzyme activities of CAT, POD, and T-SOD through its expression products; and are involved in the response of pitaya to low-temperature stress and play vital roles in this process. After ABA and MeJA treatment, the expression of HuSWEETs changed significantly, and the cold stress was also alleviated. This study elucidated the molecular mechanism and physiological changes in the SWEET gene in sugar metabolism and distribution of pitaya when it experiences low-temperature stress and provided a theoretical basis for cold-resistant pitaya variety breeding.